2017
DOI: 10.1016/j.molcel.2017.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-Translocated ACSS2 Promotes Gene Transcription for Lysosomal Biogenesis and Autophagy

Abstract: SUMMARY Overcoming metabolic stress is a critical step in tumor growth. Acetyl-CoA generated from glucose and acetate uptake is important for histone acetylation and gene expression. However, how acetyl-CoA is produced under nutritional stress is unclear. We demonstrate here that glucose deprivation results in AMPK-mediated acetyl-CoA synthetase 2 (ACSS2) phosphorylation at S659, which exposed the nuclear localization signal of ACSS2 for importin α5 binding and nuclear translocation. In the nucleus, ACSS2 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
244
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(273 citation statements)
references
References 54 publications
8
244
1
Order By: Relevance
“…5). Very recently, it was reported that AMPK-dependent phosphorylation of the lipogenic enzyme ACSS2 induced its translocation to the nucleus, where it stimulated TFEB-dependent gene expression 204 . ACSS2 has been hypothesized to control the local synthesis of acetyl- CoA pools in the nucleus to control acetylation of his-tones and other transcriptional regulators 205 (FIG.…”
Section: Ampk Regulates Autophagy and Mitophagymentioning
confidence: 99%
“…5). Very recently, it was reported that AMPK-dependent phosphorylation of the lipogenic enzyme ACSS2 induced its translocation to the nucleus, where it stimulated TFEB-dependent gene expression 204 . ACSS2 has been hypothesized to control the local synthesis of acetyl- CoA pools in the nucleus to control acetylation of his-tones and other transcriptional regulators 205 (FIG.…”
Section: Ampk Regulates Autophagy and Mitophagymentioning
confidence: 99%
“…ACSS2 is essential for protein acetylation by producing acetyl CoA, which has an important role in many biological processes. ACSS2 can increase histone H3 acetylation in specific regions, which is vital to autophagy, cell survival and tumourigenesis [28,29]. In particular, previous studies have shown that ACSS2 can promote brain carcinogenesis by increasing the expression of autophagy-related factors, such as LAMP1.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…It would be interesting to determine if AMPK-mediated activation of TFEB regulates the catalytic activity of calcineurin or interaction between TFEB and calcineurin. It has also been shown that nutrient/glucose deprivation-induced AMPK activation regulates lysosomal and autophagy gene expression through phosphorylation at S659 and nuclear localization of ACSS2 (75). Phosphorylated ACSS2 forms a complex with TFEB, which modulates lysosomal and autophagosomal genes by locally producing acetyl-CoA for histone [ 3 H] acetylation in the promoter regions of these genes.…”
Section: Discussionmentioning
confidence: 99%